Efeito de fecho em gestos de leitura do conto A Caçada, de Lygia Fagundes Telles - Mazon, Tatiani Longo (2017)
This research seeks to understand the meanings in gestures of reading and interpretation of the tale The Hunt, by the Brazilian writer Lygia Fagundes Telles. The tale was chosen due to have a suspended ending, allowing the reader to appropriate the senses and create an end that he or she considers more stable for the story. The concept of Imaginary Formations (PÊCHEUX, 1997) supports this research course by considering the possibility of new formulations from the change of position from subject-reader to author-reader in the movement of reading and interpretation of the story. In order to understand the production of meanings in the textual, discursive and social dimensions, we will analyze the closing of the story The Hunt, considering the perspectives of three areas of study: structure of fictional literary narratives, Text Linguistics (TL) and Discourse Analysis (DA). As a methodological process to understand the reading gestures, we conducted an applied research with high school students of the Heriberto Hülse School, in Criciúma/SC. The association of these three areas of study, plus Applied Linguistics (AL), brought contributions to the understanding of the short story genre functioning, such as fiction literature. The hypothesis is that, making an ending that he or she believes to be perfect for the story, makes the readers position change to author-reader, establishing new closing senses for the story The Hunt, in something that we call, in this work, of shared virtual authorship. By leaving the end of the tale open to interpretation, the author Lygia Fagundes Telles authorizes this shared participation of the reader in the movement of sense production, and this new operation differs from the reader-effect by granting the reader greater autonomy in this course. In addition to Pêcheux, this research is supported by scholars of narrative structures such as Bosi (1985), Gotlib (1985), Coutinho (1999), De Paula (1999), Jolles (1976) and Moisés (1981). In relation to TL, some authors like Fávero (1988, 2000) and Koch (1997, 2003, 2010, 2015) are responsible for the theoretical basis and in DA, we find subsidies in authors such as Furlanetto (2014, 2015), Indursky (2001,2016), Orlandi (2000, 2001, 2003, 2012) and Possenti (2009) that provide elucidations on the main themes to be developed.